If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 23 + -1x = 24 Solving 23 + -1x = 24 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-23' to each side of the equation. 23 + -23 + -1x = 24 + -23 Combine like terms: 23 + -23 = 0 0 + -1x = 24 + -23 -1x = 24 + -23 Combine like terms: 24 + -23 = 1 -1x = 1 Divide each side by '-1'. x = -1 Simplifying x = -1
| 26=7r-9 | | 17=-5(4x+2)+21x | | 7h-26=34 | | t+3-2=9 | | -2a+33+7a=3a-9a | | 2x+38+4x=180 | | a+5+1=13 | | 12x+27=6x+165 | | 12x+27=.6x+165 | | 3(5-3x)-8=88 | | 3x-3=9-3x | | x/5/8=4/15 | | 21+x=25 | | (30-6)-8-3/2 | | -9x-11=3x+25 | | 3xn=18 | | 3.7x+5=2.7x | | 1=0.2x-0.9x-20 | | 110=2x+10 | | 6x+12=3(1) | | (6xy)^4/2xy^2 | | 6y+12=3(0) | | 6y+12=3(-1) | | 1100=(30-2X)(20-X)(X) | | X+17=23-6 | | -20=4/5n | | (3a-4)/7-(2a-3)/7 | | 6y+12=3(-2) | | 2-(T/3)=T/6 | | 50(28)=7(7(28)+4) | | 7=7x-8 | | -2x-6=2x+6x |